Ferramentas para mediação de fontes de informação: avaliação sobre seus usos em bibliotecas universitárias nacionais e internacionais - Novelli, Valéria Aparecida Moreira [UNESP]; Hoffmann, Wanda Aparecida Machado; Gracioso, Luciana De Souza (Escola de Ciência da Informação da UFMG, 2014)
The study reports the use of tools for mediating of sources of information by national and international university libraries. The study was exploratory and made use of content analysis that included both a quantitative and qualitative approach of 24 selected websites from the best international and national universities libraries websites, according to some indicators, namely, Webometrics Ranking of World's Universities, World University Rankings 2011-2012 and General Index Course. The aim was to investigate and identify trends in applications of tools for activities of mediation within processes to access, search and learn the use of sources of information in university libraries. The results provide a general overview on how university libraries are conducting the mediation of sources of information, with special regards to bibliographic databases. Variations in the scale of implementation of these tools among international and national libraries as well as some examples of tools could be highlighted. One may conclude that, given the availability and increasingly growing accessibility of sources of information, it is necessary to use them effectively and efficiently. Within this context, it is up to the librarian to reflect upon, select and implement the most feasible actions and tools more viable of the each library's reality, taking into account specific particularities of generations and types of users, diversity of technology offered to these users as well as to non-users, autonomy, encouragement and facilities to access, search and use of sources of information.

A pesquisa relata o uso de ferramentas para mediação de fontes de informação por bibliotecas universitárias nacionais e internacionais. O estudo foi de caráter exploratório e utilizou análise de conteúdo, com abordagem quantitativa e qualitativa, de websites de 24 bibliotecas selecionadas dentre as melhores universidades internacionais e nacionais segundo indicadores da Webometrics Ranking of World's Universities, World University Rankings 2011-2012 e Índice Geral de Cursos. Objetivou-se investigar e identificar tendências de aplicações de ferramentas para as atividades de mediação dos processos de acesso, busca e aprendizagem do uso de fontes de informação em bibliotecas universitárias. Os resultados apontam um panorama geral de como as bibliotecas universitárias estão realizando o processo de mediação de fontes de informação, especialmente em relação às bases de dados bibliográficas. Observou-se variações na escala de implementação dessas ferramentas entre as bibliotecas internacionais e as bibliotecas nacionais, bem como o destaque de algumas delas. Conclui-se que diante da disponibilidade e acessibilidade cada vez mais crescente das fontes de informação, torna-se necessário que estas sejam utilizadas de forma eficaz e eficiente. Neste contexto cabe ao bibliotecário refletir, selecionar e implementar ações e ferramentas mais viáveis à realidade de cada biblioteca, considerando as características específicas das gerações e categorias de usuários, a diversidade de tecnologias ofertadas a estes usuários e também aos não usuários, autonomia, estímulo e facilidades para o acesso, busca e uso das fontes de informação.
Tools for mediating of sources of information: an evaluation of their use in national and international university libraries
Keywords: Bases de Dados Bibliográficas; Bibliotecas Universitárias; Fontes de Informação; Mediação da informação; Bibliographic Database; University Libraries; Sources of Information; Mediation of Information